A felnőttképzés jellemzői II. rész : A képzés és fejlesztés vállalaton belüli módszerei - Gulyás, László (Közép-Európai Közlemények, 2014)
The knowledge-based society and economy has a new demands from employee. The long life learning is becoming reality. Where upon the theory and practice of training and development is growing day after day. HR-managers, HR-specialist and researchers produced several models and methods of training and development. There can be sorted two big groups: 1.On the job methods, 2.Off the job methods. Recent essay is dealing with the theory of “on the job” methods. Accordingly we review the Hungarian HR-books and essays dealing with “on the job” methods. We examine the advantages and disadvantages of different methods, sort and evaluate them.